Geospatial Analysis: A New Window Into Educational Equity, Access, and Opportunity. Issue 1 (March 2020) - Cobb, Casey D.
A robust body of geographic education policy research has been amassing over the past 25 years, as researchers from a variety of disciplinary backgrounds have recognized the value of examining education phenomena from a spatial perspective. In this chapter, I synthesize 42 studies that examine education issues using a geographic information system, or GIS. The review is framed by the major thread that runs through this body of research: educational equity, access, and opportunity. I summarize the research within seven theme-based research topics and offer examples of geospatial analysis as applied to education. The chapter includes a discussion of the major barriers and limitation facing GIS researchers and offers thoughts about the future.